Sonication pretreatment of sludge: preliminary study of sludge conditions - Le, Ngoc Tuan; Julcour-Lebigue, Carine; Delmas, Henri (Vietnam Journal of Science and Technology, 2015)
The objective of this work was to investigate effects of sludge conditions serving sludge ultrasonication (US). First, it is confirmed specific energy input (ES) plays a key role in sludge disintegration (DDCOD). An optimal total solid concentration of 28 g/L was found to be convenient for sludge US pretreatment. Besides, secondary sludge showed the highest disintegration, followed by digested and mixed sludge regardless of temperature (T) control during US. Additionally, pH adjustment -addition of low NaOH dose (22-40 mgNaOH/gTS) could be useful, that significantly improved COD release under subsequent US while resulting in a suitable pH value for anaerobic digestion afterwards.